(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
We propose to revisit the teaching-learning experiences carried out within the scope of a curricular component of the Theatre Teacher Education Program at URCA. Taking as epistemological guiding lights the reflections developed by Luiz Rufino (2019) and Luiz Antonio Simas (2019) in the field of decolonial education in recent years, we arrived at two different pedagogical propositions: in one of them, street child plays were adopted as an educational tool to explore the relations between childhoods and the city; in the other one, the contact with a master of popular knowledge unfolded into artistic-pedagogical practices in Theatre. These are the propositions we present and discuss on this occasion.